Fermenting Futures: Food Fermentation as an ‘Art of Noticing’ - Modi, Kaajal (Journal of Posthumanism, 2023)
In this paper I explore the material and metaphoric affordances of fermentation as an “art of noticing” (Tsing, 2015) as embodied through a collaborative practice of making with migrant women of colour in the kitchen. In doing so, I make visible some of the ways in which our microbial entanglements make us part of our environments, and the ways in which these have the potential to connect us to planetary metabolic ecologies. Through this practice, I further work to disrupt the exclusion of marginalised people from the category of human by challenging the basis of individualism and the idea of human as a discrete category. I do so by utilising food fermentation to consider the ‘cross-cultural’/multispecies ethics at play as a heuristic for a mode of participation that can account for diverse modes of knowledge and agency. By working with and valuing the disparate knowledge, stories and cultural practices of women from formerly colonised nations, I create space for joy, experimentation and play in what Villalba (2019) calls temporary “bubbles… in which to cultivate the future.